Interactive learning environment for kids - Mohd Hanif, Mohd Ali (2011)
Multimedia play important roles in learning process. In traditional primary level learning process in Malaysia, multimedia is not fully implemented yet.So the teachers use traditional material to teach student and this affects the result of student.So,the new way to teach student may change the way of learning environment to become more interactive, collaborative and fun.Interactive learning environments give the new experience of students in classrooms by allowing them to explore information and to use what they discover to construct knowledge in their own words. Interactive Learning Environment using Multiple Mouse is a type of multimedia learning system that has been developed and aimed for the primary school children; those have a problem with their learning process and the collaborative in classroom.